Effective chemotherapy and targeted therapy supplemented with stereotactic radiotherapy of a patient with metastatic colon cancer following renal transplantation: a case report - Bellyei, Szabolcs (J Med Case Rep, 2021)
BACKGROUND: Previous studies have shown that patients who underwent renal transplantation were at a greater risk of developing malignancies. Due to advances in effective surgical techniques and immunosuppressive therapies, organ recipients live longer. Yet, there is insufficient information about the recommended type of therapy for colorectal cancer patients following transplantation. We describe the oncological treatment of a patient with renal transplantation, who presented with metastatic colon cancer 5 years after transplantation. CASE PRESENTATION: A 66-year-old Caucasian male patient, with hypertension, type 2 diabetes mellitus, paroxysmal atrial fibrillation, and renal failure underwent successful kidney transplantation in 2013. In April 2018, the adenocarcinoma of the sigmoid colon was found, and surgical resection was performed. The histological diagnosis was low-grade adenocarcinoma. Fluorodeoxyglucose positron emission tomography/computerized tomography scan showed a 2.5-cm metastasis in the VIIth segment of the liver and a metastatic paraaortical lymph node on the left. The clinical diagnosis was, therefore, metastatic (stage IV) sigmoid colon cancer (AJCC TNM system). The ongoing medications of the patient included immunosuppressive drugs and medication for his cardiovascular comorbidities. In July 2018, palliative cetuximab plus folinic acid–fluorouracil–irinotecan chemotherapeutic treatment was initiated, then cetuximab was substituted for panitumumab because of adverse events. In August 2018, the follow-up positron emission tomography/computerized tomography scan revealed stable disease. Because of side effects, the patient was unwilling to continue with the panitumumab plus folinic acid–fluorouracil–irinotecan treatment regimen. Therefore, the patient received 10× 5 Gy stereotactic body irradiation for his liver metastasis and mono-panitumumab therapy. By January 2019, the positron emission tomography/computerized tomography scan showed regression of the liver metastasis but a progression in the paraaortic lymph node. Therefore, 5× 8 Gy stereotactic irradiation was given to the paraaortic lesion. Meanwhile, the patient received altogether 16 cycles of panitumumab until June 2019, when complete remission was attained. In July 2019, the patient suffered a hemorrhagic stroke, probably due to his cardiovascular comorbidities, and died subsequently. CONCLUSIONS: Since information is scarce regarding oncological treatment of patients following organ transplantation, data about their oncological treatment is essential. To our knowledge, this is the first case report to describe the successful chemotherapy and targeted therapy supplemented with stereotactic radiotherapy of a posttransplant patient with metastatic colorectal cancer.